Avaliação da resposta imune um ano pós-vacinação com Coronavac em idosos e profissionais em instituições de longa permanência - Santos, Joyce Thayane da Conceição dos (2024)
Risk groups such as the elderly and individuals with comorbidities are associated with the most severe forms and higher mortality rates of coronavirus disease (COVID-19). Research institutes around the world have focused efforts on the development of vaccines to control the pandemic, aiming to establish immunological memory against SARS-CoV-2 (severe acute respiratory syndrome from coronavirus-2), and reduce severe cases of the disease. This study aimed to evaluate humoral and cellular immunity in elderly people and professionals from long-term care facilities in Sergipe, one year after vaccination against COVID-19. Humoral immunity was assessed using fluorescence immunoassay to quantify total anti-SARS-CoV-2 IgG and IgM antibodies and neutralizing IgG (nAb). Cellular immunity was assessed using flow cytometry immunophenotyping, using the Attune NxT cytometer and FlowJo software.The analysis strategy was the phenotypic and functional characterization of populations of CD4+ and CD8+ T lymphocytes, naïve and memory (CD45RA/CCR7), and NK lymphocytes (CD69). 175 individuals were evaluated, 139 of whom were elderly and 36 that were professionals. The majority were female (64%), with ages ranging from 60 to 102 years old (M=79.4) and from 26 to 50 years old (M=42) (p <0.00001). It was observed that the average anti-SARS-CoV-2 neutralizing antibody tests were similar in both groups, 98.5% in the elderly group and 100% in the professional group (p=0.1306), demonstrating a strong response to the virus SARS-CoV-2. IgM antibodies were detected in 35% of elderly people and 22% of professionals, while IgG antibodies were detected in 85% of elderly people and 94.4% of professionals.In the longitudinal analysis 90 days (D90) and 360 (D360) days after vaccination, it was observed that the presence of nAb was higher on D360 with 100% in both groups, and only 63% of the elderly and 65.2% of the professionals on the D90. IgG antibodies were detected in 77% (D90) and 90% (D360) of the elderly, and 87 and 100% of professionals respectively (p=0.0371 and 0.0035), suggesting a beneficial effect of the booster dose in vaccination. Cellular immunity was assessed in 19 individuals, 12 elderly people aged between 65 and 89 years (M=77), and seven professionals aged between 24 and 59 years (M=40). An increase in the expression of CD4+ T lymphocytes was demonstrated in the elderly compared to professionals, with the Effector Memory phenotype being more pronounced in the elderly. Among CD8+ T lymphocytes, the naïve phenotype showed reduced expression in the elderly group. Analysis of natural killer (NK) lymphocytes showed an increase in the expression of activated NK lymphocytes in the elderly. In conclusion, there was no difference in the humoral immune response between the elderly and professionals, suggesting the effectiveness of vaccination regardless of age. Furthermore, cellular analysis revealed that the elderly had a higher expression of CD4+ T lymphocytes, especially effector memory lymphocytes, and activated NK lymphocytes. These results contribute to the understanding of the immune response, in the development of vaccination strategies to protect the population from the most serious forms of COVID-19, especially the most vulnerable groups.